State, Religion and COVID-19: can Religious Freedom be Guaranteed in Exceptional Circumstances? (Stato, Chiese e pluralismo confessionale, 2022)
TABLE OF CONTENTS: 1. The coronavirus crisis: a tragedy and an opportunity - 2. Demanding governments’ accountability - 3. The conditions for legitimate restrictions on freedom of religion or belief - 4. The significance of equality and State’s neutrality for the protection of religious freedom - 5. Advantages of dialogue and cooperation between State and religion - 6. Support and doubts in the reaction of religious communities to governmental measures - 7. Final remarks.ABASTRACT: This article explores peculiarities of the COVID-19 pandemic in comparison to other health crisis experienced in the past. Each character is thoroughly examined in the article. The article focuses on four thematic areas: the legal regulation of the fight against coronavirus; the equality of treatment of religious freedom in relation to other fundamental rights; the cooperation between the State and religious communities; and the reactions of religious communities to governmental measures. The article argues that rather than raising new questions, COVD-19 has forced us to deal with familiar questions under unprecedented circumstances. In this frame, time has played a central role as a factor to be taken into account to scrutinize the legitimacy of measures introducing severe limitations to fundamental rights and freedoms. Finally, the article claims that from a legal perspective, the experience of the past months reveals that, especially in times of crisis, we need a scrupulous respect for the requirements of the rule of law, including a strict accountability and transparency from governments, and putting especial emphasis on the protection of fundamental rights, among which is freedom of religion or belief.